THE INFLUENCE OF HEALTH PROMOTION ON THE LEVEL OF KNOWLEDGE AND ATTITUDE REGARDING CLEAN AND HEALTHY LIVING BEHAVIOR - Farida, Siti Nur; Hidayah, Ardiyanti; Anggraini, Rista Dian (Literasi Kesehatan Husada: Jurnal Informasi Ilmu Kesehatan, 2024)
Background: The elementary school age period is often referred to as the intellectual period. At the developmental stage, elementary school children are 6-12 years old. During this period, children are relatively easier to educate than before and after. During this period, children are more likely to experience various kinds of diseases. Health problems that often occur in children are caused by a lack of clean and healthy living behavior. Health promotion is an effort in health education in schools. Objectives: The aim of conducting this research is to determine the effect of health promotion on children's knowledge and attitudes about PHBS. Design: This research method uses a pre-experimental one group pretest and posttest design. Methods: This research was carried out in August 2023 at SDN 3 Mancar, Peterongan, Jombang Regency. The population in this study was all students in grades IV and V at SDN Mancar 3, Peterongan, Jombang Regency, totaling 47 students and the sample in the research was some students at SDN Mancar 3, Peterongan, Jombang Regency, totaling 42 respondents. The sampling technique uses purposive sampling. This research instrument uses a questionnaire and instruments for health promotion using an outreach program unit (SAP). The statistical test used is the Marginal Homogeneity test using SPPS 19 for Windows with a significance level of 0.05 (95% confidence level). Results: The results of statistical tests stated that the respondents' PHBS knowledge before treatment was in the sufficient category (40.5%). After treatment, respondents' knowledge was in the good category (50%). Before treatment, the PHBS attitude of respondents was in the good category (61.9%). After treatment, respondents' attitudes increased to the good category (85.7%). The statistical results of respondents' knowledge show a p-value of 0.000 and the respondents' attitudes show a p-value of 0.008, which means that there is an influence of health promotion on children's knowledge and children's attitudes about PHBS. Conclusion: Based on the results of this research, it is hoped that health workers can provide health information to improve students' knowledge and attitudes in carrying out PHBS.